Against climate apartheid: Confronting the persistent legacies of expendability for climate justice. (June 2022) - L Rice, Jennifer; Long, Joshua; Levenda, Anthony
While the uneven causes and impacts of climate change are widely known, it is also becoming evident that many elements of the response to the climate crisis are also reinforcing discrimination, segregation, and displacement among marginalized peoples. This is entrenching a system of climate apartheid, one that is evidenced by uneven vulnerabilities to the climate crisis, as well as inequitable implementation of climate-oriented infrastructures, policies, and programs. These efforts often secure privileged populations while harming, excluding, and criminalizing populations whose lives have been made precarious by climate change. Like previous incarnations of state-sponsored "separateness, " climate apartheid is rooted in processes of colonization, racial capitalism, and hetero-patriarchy that render some populations expendable. In this paper, we show how these interlocking historical structures of oppression facilitate a response to climate change that is systematically promoting spatial, socio-economic, and ecological segregation in many mainstream attempts to safeguard economic and socio-political structures amidst global ecological catastrophe. We then offer frameworks and interventions intended to introduce meaningful pathways forward for climate justice that seek to render all life indispensable.